Educational Leadership Strategies In Facing The Challenge of Learning Loss in Sophos Preschool Indonesia - Dian Farrini; Syifa’ Nurda Mu’affa; Syifa Sayla Ramadhani; Jejen Musfah (Universitas Batanghari, 2022)
The purpose of this study is to analyze the strategy of Sophos Preschool Indonesia in preventing learning loss. This research uses qualitative approaches and descriptive methods. Data is collected with the interview, observation, and documentation techniques. The data analysis technique used in this study is qualitative analysis as proposed by Miles and Huberman, namely data collection, data reduction, data presentation, and conclusion withdrawal. The data validity in this study was done by triangulation, namely source triangulation and triangulation methods. This study concludes that the strategy carried out by the Head of Sophos Preschool Indonesia succeeded in preventing learning loss. The strategy consists of three steps as proposed by Fred R. David, namely strategy formulation, strategy implementation, and strategy evaluation. These three steps succeeded in preventing learning loss in Sophos Preschool Indonesia.